Mapping the Customer Experience Management Strategies for Customer Loyalty in Retail Hypermarket Jabodetabek - Logahan, Jerry Marcellinus; Meliala, Janita Sembiring; Putong, Iskandar (Journal the Winners: Economics, Business, Management, and Information System Journal, 2015)
Today, competition in the global market has become increasingly difficult and and at the same time products and services provided by retail companies tend to be similar. So in such circumstances, customers expect not only satisfied with the products and services, but also the pursuit of the perfect shopping experience during the shopping process. The purpose of this study was to devise a customer experience management strategy at a hypermarket retailer Carrefour, Hypermart, Giant, and Lotte Mart. Both overall and per hypermarket retail chains that have the same character. The method used is Factor Analysis, Multi Dimension Scaling (MDS). The object of research is the hypermarket retail customers in Jakarta, Bogor, Depok, Tangerang and Bekasi to sample 360 people. The results of MDS mapping CEM variable per retail hypermarket retail hypermarket seen no one who is in the first quadrant in which the dimensions 1 and 2 positive namely Gianthypermarket retail. Tthere are three retail hypermarket located in quadrant 2 wherein the dimensions of 1 positive and 2 negative dimension namely retail Carrefour, Hypermart and Lotte Mart. In MDS can be classified Group 1 are the outlets; Group 1 are GPS (Giant Plaza Semanggi), CLB (Carrefour Lebak Bulus), CPH (Carrefour Permata Hijau) and HPV (Hypermart Pejaten Village) which leads to a positive value. While other outlets in group 2 are CCB (Carrefour Cibinong Bogor), GBT (Giant BSD Tangerang), GMD (Giant Margo city Depok), HPB (Hypermart Pondok Gede Bekasi), HJT (Hypermart JACC Thamrin), LRP (Lotte Mart Ratu Plaza), LKG (Lotte Mart Kelapa Gading), LF (Lotte Mart Fatmawati) have in common in the lower quadrant (negative).